Regionalitás és településszerkezet (Egy shift-analízis eredményei) - Gulácsi, Gábor; Nemes Nagy, József (Tér és Társadalom, 1989)
Using seven indices of (infrastructural) supply, the authors seek to answer the question: what is the role of settlement structure (Ti) and the varied level of supply by settlement types (Ri) differentiating the level of supply of the 19 counties in Hungary. The role of specific features ef counties, i.e. the regional factor (Ri) was found to be dominant by the analysis. The study reveals contrasted regional duality between the western (developed) and the eastern (underdeveloped) regions of Hungary. Today such socio-economic mechanisms seem to have come into gear in Hungary which may develop the mentfonal dualism beyond the realm of infrastructural supply, into an overall spatial development process. New, all-embracing regional policy ideas and practice are needed to stop these process leading to extreme spatial separation.